USING NUMBERED HEADS TOGETHER COOPERATIVE LEARNING AS SPEAKING STRATEGY - Andre Bona Josua Panjaitan; Ikhsan Ramadhan Hasibuan; Yenita Sembiring (elt, 2021)
This study aims to determine the students' ability to speak English with the classroomaction research technique to change the model of student learning with the Numberedheads together method. The research is SMK Telkom 2 Medan class X, there are stillmany students who can't speak English and lack confidence in their abilities. We asresearchers look for the problem points in these students and choose technical methodsthat make them active and can speak English. using the NHT method as a guide becausestudents are more active in learning with groups, with this method the level of students'speaking ability is increasing. Before using this method only 25.7% of students' ability tounderstand it. While after using this method 70.33% of students' increase in studentability. from si This method is very active for students because students learn in groupsmore actively and so they get satisfactory results. This research has a special ability,namely changing the learning system of students who do not understand, uniting themwith students who understand, and making them into competent teamwork. The problemthat occurred during this lesson was because of the COVID-19 pandemic, students werelearning online which made them a little constrained, but with the help of the school tostudy face-to-face, they became active in learning English.Keywords : English, technique, NHT, method, learning, and teamwork